2012
DOI: 10.1007/s12262-012-0566-9
|View full text |Cite
|
Sign up to set email alerts
|

Giant Male Fibroadenoma: A Rare Benign Lesion

Abstract: Fibroadenoma, the most common breast tumor in adolescent women, usually arises in the terminal duct lobular unit, but is exceedingly rare in the male breast. The usual presentation is a painless, firm, mobile, and slow-growing lump in the breast of a woman of childbearing age. Its diagnosis is usually made by clinical examination, but ultrasound, mammography, and fine-needle aspiration often help in its confirmation. We are presenting here a rare but interesting case of a large fibroadenoma, which was present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…Here, we present an elderly man with a left breast fibroadenoma alongside a history of ischaemic heart disease and associated severe complications. Notably, most fibroadenomas in men demonstrate a strong association with gynecomastia,5–18 which was not present in our patient.…”
Section: Introductioncontrasting
confidence: 45%
“…Here, we present an elderly man with a left breast fibroadenoma alongside a history of ischaemic heart disease and associated severe complications. Notably, most fibroadenomas in men demonstrate a strong association with gynecomastia,5–18 which was not present in our patient.…”
Section: Introductioncontrasting
confidence: 45%
“…2 There appears to have been approximately only 15 cases of male fibroadenoma reported in the English literature to date (Table 1). [3][4][5][6][7][8][9][10][11][12][13][14][15] It has been suggested that proliferative changes in the male breast, such as gynecomastia and fibroepithelial lesions, are caused by hormonal imbalances or medications not primarily intended to target the breast. Fibroadenomas are known to have both estrogen and progesterone receptors, 11 and most of the reported male fibroadenomas have occurred in male-to-female transgender patients or patients receiving estrogen therapy for a medical condition such as prostate carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…On FNAB, many stromal cells with bare bipolar nuclei are seen on smear. Many sheets of uniform single cells arranged in staghorn pattern are seen as honeycomb appearance [9]. FNAC of male breast lesions only few studies are there and most have described distinction between gynecomastia and carcinoma [3].…”
Section: Discussionmentioning
confidence: 99%